Measurement of Radon Activity Concentration in Soils Samples of Shaqlawa Region in Erbil City/ Iraqi Kurdistan Using RAD7 Detector - Yusra Mala Yousif Muhammad; Preshan Khder Fatah; Sardar P. Yaba (Zanco Journal of Pure and Applied Sciences, 2023)
The radon concentration of soil samples from several places in the Shaqlawa city/Iraqi Kurdistan area has been determined by using RAD7detector. The soil samples are gathered from different geological formations. Maximum and minimum radon concentrations were (88.3 ± 9.4) and (51.1 ± 7.1) Bq/m3 in the regions of Kawanian and Darband , respectively. The average radon concentration in soil samples from the city of Shaqlawa was (63.15 ± 16.94) Bq/m3, which was below the ICRP-recommended threshold (1991).